Poor-tasting pediatric medicines: part 2. Exploring caregiver and healthcare provider values and preferences for a novel taste-blocker product to improve acceptability - El-Sahn, Moushira; Elliott, Rose; El-Sahn, Mona; Lucas, Izaak; Kong, Karen; Walsh, Jennifer; Lucas, Jeff (Frontiers in Drug Delivery, 2025)
IntroductionImproving the palatability of bitter-tasting medication for pediatric populations has long presented a challenge. Taste blockers are being researched as a potential solution; however, end-user perspectives and needs related to this concept have not been explored. The objectives of this research were 1) to understand current experiences of administering bitter-tasting medication; 2) the evaluation of a consumer-targeted product profile (CTPP) for a taste blocker including attributes such as form and duration of action; and 3) whether there is a need to support improved acceptability and adherence with a taste blocker taken before the bitter-tasting medication.MethodsOur study consisted of simultaneous qualitative and quantitative phases, involving caregivers and healthcare providers with experience administering medications to children aged 2–17 years. Qualitative research was conducted with 120 caregivers and 92 healthcare providers using a range of methods. Focus groups (FGs) were conducted in Kenya, Nigeria and Zimbabwe (grouped as Sub-Saharan Africa (SSA) but not intended to be representative of the region as a whole) with caregivers of children who had taken medication for HIV, TB, pneumonia, or malaria (including for seasonal prevention) within the past 6 months. Telephone in-depth interviews (TDIs) were conducted with caregivers of children with chronic illnesses in the United States. Face-to-face in-depth interviews (IDIs) and TDIs were conducted with healthcare providers. The quantitative part of the study was conducted with n = 1,815 caregivers and n = 859 healthcare providers using face-to-face computer-assisted interviews (CAPI) in SSA, and via online panel research in the United States A CTPP was used as the stimulus for discussion. Participants were asked about their experiences in giving bitter-tasting medication to their children or patients, their perceptions of and willingness to try a taste blocker, and their preferences for specific product attributes.ResultsParticipants described how bitter-tasting medications create challenges in multiple areas: for caregivers, children, their daily life and routines, healthcare providers, and children’s perceptions of healthcare. In SSA, 28.9% of caregivers reported that their children always or regularly refused medication due to bitter taste, while 57.9% reported this in the United States. Another 36.2% and 29.1% respectively experienced this sometimes or occasionally. Over 80% of providers in all countries stated that bitter taste impacts adherence to both long and short-term medication. The preferred attributes of the taste blocker were a sweetened and flavored lollipop form with a maximum total duration of up to approximately 1h, and with a total taste block achieved as soon as possible. Overall, responses to the concept of the taste blocker were positive from caregivers and providers, with a perception that it would make administering bitter-tasting medication easier. Over 90% were positive about using or prescribing the taste blocker in SSA, while in the United States, over 90% of caregivers were positive about using it, as were over 70% of providers about prescribing it. Concerns centered around the duration of the absence of the sense of taste, and the effects this might have on children’s appetite; there were also concerns that repeated taste blocking might have a long-term impact on children’s sense of taste.ConclusionThe results of the study indicate that there is a high perceived need for a taste blocker to aid in administering bitter-tasting pediatric medication. Concerns around duration and potential impact of long-term use must be addressed.